2021
DOI: 10.3390/su13147590
|View full text |Cite
|
Sign up to set email alerts
|

Decay Process Characteristics and Fungal Community Composition of Salix psammophila Sand Barriers in an Arid Area, Northern China

Abstract: With the increase in setting years in deserts, Salix psammophila sand barriers with different degrees of lodging damage caused by decay are losing wind-prevention and sand-fixation properties. In this study, we focus on the change in chemical properties of soils, and physical and mechanical properties of plants along different setting years; meanwhile, the change in fungal communities has been analyzed using high-throughput sequencing technology. The results show that a change in physical and mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Some scholars have also found that SL checkerboard barriers have been irreversibly damaged over time due to microbial or fungal influences on the biological structure and chemical composition of the sand-buried section. The structure and composition can alter the nutrient characteristics of the soil [49][50][51][52]. In this study, soil nutrients were higher in the bottom position of the checkerboard barrier dunes than in other parts of the dunes because the bottom position of the SL barrier dunes and HDPE barrier dunes belonged to the weak wind erosion zone compared with the middle and top parts of the dunes, which was more conducive to soil nutrient enrichment.…”
Section: Soil Nutrient Characteristics Of Dunesmentioning
confidence: 60%
“…Some scholars have also found that SL checkerboard barriers have been irreversibly damaged over time due to microbial or fungal influences on the biological structure and chemical composition of the sand-buried section. The structure and composition can alter the nutrient characteristics of the soil [49][50][51][52]. In this study, soil nutrients were higher in the bottom position of the checkerboard barrier dunes than in other parts of the dunes because the bottom position of the SL barrier dunes and HDPE barrier dunes belonged to the weak wind erosion zone compared with the middle and top parts of the dunes, which was more conducive to soil nutrient enrichment.…”
Section: Soil Nutrient Characteristics Of Dunesmentioning
confidence: 60%
“…Detailed steps were described by Wu et al(2021). The cellulose content was determined by the nitric acid-ethanol method (Yang et al, 2021). Brie y, samples (0.75 g) were added to 25 mL of nitric acid-ethanol (4:1, v/v), heated for 1 h in a boiling water bath with stirring every 10 min, centrifuged at 6000 rpm for 5 min at 4 ℃ on an H1850R centrifuge (Hunan Xiangyi Laboratory Instrument Development Co., Ltd., China) to remove the supernatant uid, and repeated once.…”
Section: Lignin Cellulose and Hemicellulose Determinationmentioning
confidence: 99%
“…We selected a part of the crushed S. psammophila sand barrier samples to be dried in a drying oven at 80 • C after passing through a 40-60 mesh sieve in order to more accurately weigh the constant weight of the samples. Cellulose content was determined by a nitric acid-ethanol method, hemicellulose was adjourned application a hydrochloric acid-DNS abbreviation amoroso method, and lignin was bent application a concentrated sulfuric acerbic band-aid adjustment at an absorption of 72% (Xiong et al, 2005;Wang and Cheng, 2011;Zhang et al, 2016;Yang et al, 2021).…”
Section: Analysis Of Main Chemical Componentsmentioning
confidence: 99%